ANALISIS STRUKTUR KAMUS DWIBAHASA LAMPUNG—INDONESIA [Structural Analysis of The Lampung—Indonesian Bilingual Dictionary] - yulfi zawarnis (Kantor Bahasa Provinsi Maluku, 2019)
This paper is the result of an analysis of the structure of the Lampung-Indonesian bilingual dictionary. The data is examined by a number of entries in the Bilingual Lampung Dictionary - Indonesia. The method used is a descriptive analytical qualitative method with an objective approach that aims to provide an overview of reality in the object studied. Data were analyzed based on groups of data adjusted for type and type of error. The results of the analysis show that the Lampung-Indonesian Bilingual Dictionary published by the Lampung Province Language Office in 2009 still needs to be revised. Things that must be present, not yet appropriate, or need to be omitted in the dictionary are the inclusion of word classes, phonetic symbol omissions, uniformity of defining systems, and uniformity of writing symbols of sound / kh / and / gh / to / r /. In addition, the entries contained in the dictionary are still very limited in number. Based on the results of the analysis, it can be concluded that the Lampung Bilingual Dictionary - Indonesia still requires revisions so that benefits can be felt. Makalah ini merupakan hasil analisis terhadap struktur Kamus Dwibahasa Lampung—Indonesia. Data yang dikaji sejumlah lema yang terdapat dalam Kamus Dwibahasa Lampung—Indonesia. Metode yang digunakan adalah metode kualitatif deskriptif analitik dengan pendekatan objektif yang bertujuan memberikan gambaran tentang realitas pada objek yag diteliti. Data dianalisis berdasarkan kelompok data yang disesuaikan dengan tipe dan jenis kesalahan. Hasil analisis menunjukkan bahwa Kamus Dwibahasa Lampung—Indonesia yang diterbitkan oleh Kantor Bahasa Provinsi Lampung pada tahun 2009 masih perlu direvisi. Hal-hal yang harus harus ada, belum sesuai, atau perlu dihilangkan dalam kamus tersebut adalah pencantuman kelas kata, penghilangan lambang fonetik, penyeragaman sistem pendefinisian, dan penyeragaman penulisan lambang bunyi /kh/ dan /gh/ menjadi /r/. Selain itu, lema yang terdapat dalam kamus tersebut masih sangat terbatas jumlahnya. Berdasarkan hasil analisis tersebut disimpulkan bahwa Kamus Dwibahasa Lampung—Indonesia masih memerlukan revisi agar dapat lebih dirasakan manfaatnya